TINJAUAN DANA TABARRU DALAM PRODUK TAKAFUL - Namira Irza Andari, Pratiwi Kurniati, Metayana Taufani Sitohang, (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2019)
This paper, discusses the position of Tabarru’ funds in Islamic insurance. The problem raised is how the position of tabarru’ funds in insurance Sharia is said to be purely an element of help. The aim is to analyze and understand the 'true tabarru fund concept', and to find out about sharia insurance and the position of tabarru funds' in sharia insurance. This research is a descriptive approach literature study (library research). From the results of this study concluded that sharia insurance is a sharia-based financial institution and tabarru funds' are part of the customer's investment funds deposited to the sharia insurance financial institution. The position of Tabarru funds for Islamic insurance is the core of the existence of Islamic insurance that cannot be separated. The basis for the implementation of sharia insurance regarding tabarru funds' cannot be released from the DSN-MUI fatwa number 21 / X / 2001 concerning general guidelines for sharia insurance and in DSN-MUI Fatwa Number 53 / DSN-MUI / III / 2006 concerning tabarru agreement. Keywords : Sharia Insurance, Tabarru Fund, Tabarru Agreemen